Students' perception of the course Pedagogy - Hernando, Harivelle Charmaine T.
This study conducted at the UP College of Medicine was geared primarily to evaluate the effectiveness of the course Pedagogy I offered to first year medical students. In this respect, this study is focused at answering the following questions based on the students' perception: 1) Were objectives of the course attained?, 2) Was the course effectively implemented?, 3) Were the teaching strategies used effective in delivering the content? The Context-Input-Process-Product model by Stufflebeam (1971) was used as the conceptual framework, specifically zeroing in on the Product (attainment of goals and objectives) and Process (teaching strategies) evaluation components of the model. The sample comprises 130 student respondents to a questionnaire from Class 2000. Although they are all Year Level III students in the UPCM, they had varied backgrounds during their preparatory medicine years. These data were supplemented by interviews on selected students of upper year levels, faculty members who have taught as well as those who have not taught the course, and administrative personnel. The data used in the study were obtained at the end of the course using questionnaires and interview sessions. These included their perceptions on: attainment of course objectives, course implementation, their major learning, effective topics and activities, course materials, physical setting, length of session hours and group facilitators. Frequencies and percentages were employed in presenting the ratings and perceptions of the respondents for a descriptive analysis of the problem. The principal findings of the study are as follows: 1) majority of the respondents perceived that the objectives of the course have been attained, 2) majority of the respondents perceived that the course was effectively implemented based on the following: a) they were able to cover the materials and perform the activities within the allotted time; b) the course content and activities were clearly presented; c) the teaching strategy (small group discussion) was effective; 3) the setting for small group discussion should have a definite place conducive for learning, 4) the facilitators were approachable, accommodating and good. The course had been generally effective in attaining objectives. However, in view of the findings derived, it is recommended that appropriate steps be undertaken to remedy the physical set-up and continuous monitoring of the course for future improvement.